PHILOSOPHY OF JAVA GRAPYAK, SEMANAK ORA NRANYAK AS AN EFFORT TO BUILD THE CHARACTER OF STUDENTS AT SMP KARTIKA XII-1 MERTOYUDAN KAB. MAGELANG - Imam Mawardi; Laeliya Hikmawati Laeliya Hikmawati; Budi Warsana; Nur Muhammad Iqbal (Jurnal Mantik, 2022)
Through teaching and learning activities in schools, the purpose of character education related to mental cultivation and attitudes of students is formed through the cultivation of positive Javanese philosophical values, namely Grapyak, Semanak ora Nranyak. In addition, seeing the phenomenon of the negative impact caused by Covid-19, the formation of the guiding character of the ancient Javanese society is very much in line with morals. Through the habituation method that has begun to be carried out in a coordinated manner between OSIS administrators and students of SMP Kartika XII-1 Mertoyudan, one of the goals is to revive the ancient Javanese philosophy of social ethics in the school environment, which is expected to be continued by students in the community and participating families educate. This type of qualitative research is direct research in the Kartika XII-1 Mertoyudan Junior High School environment using the methods of observation, interviews and documentation. The results of the author's analysis, that the formation of the Javanese philosophical character of Grapyak sumanak ora Nranyak through the habituation method at SMP Kartika XII-1 Mertoyudan Kab. In Magelang, indicators of student attitudes that appear in the school environment include the relationship between students and teachers, junior high school employees, seniors, peers with a good percentage of 70% and poor results 30% so that the implementation of gapyak, semanak ora tranyak continues. motivated so that students have more harmonious social relationships